Genes das espermadesinas de caprino (Capra hircus): clonagem molecular e perfil de expressão no trato reprodutor masculino - Melo, Luciana Magalhães (2007)
The male genital tract expresses distinct classes of genes, whose proteins are involved in the remodelling of the sperm surface, which occurs during sperm transit through the genital tract and continues after ejaculation [...]